2004
DOI: 10.1002/art.20474
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in rheumatoid arthritis

Abstract: Objective. To examine the level of anxiety experienced by individuals with rheumatoid arthritis (RA).Methods. Data from 2 previous studies were used to compare the level of anxiety (measured by the State-Trait Anxiety Inventory) in the following 4 subgroups: a general RA sample, a general osteoarthritis sample, a sample with both RA and major depression, and a normative sample of age-equivalent, working adults. Canonical correlations were used to examine associations between measures of anxiety and measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 28 publications
3
86
0
5
Order By: Relevance
“…3 Anxiety symptoms and disorders have been less studied separately, because they are a very frequent dimension of depression, making it difficult to separate anxiety symptoms from depressive ones. 10 Some studies have found a prevalence of almost 40% of anxiety symptoms in RA. 11 Two main hypotheses have been proposed to explain the association between RA and depressive manifestations: 1) the functional disability and poor quality of life could provoke the emergence of depressive symptoms or 2) a common neuroimmunobiological mechanism could underlie the development of RA and depression.…”
Section: Introductionmentioning
confidence: 99%
“…3 Anxiety symptoms and disorders have been less studied separately, because they are a very frequent dimension of depression, making it difficult to separate anxiety symptoms from depressive ones. 10 Some studies have found a prevalence of almost 40% of anxiety symptoms in RA. 11 Two main hypotheses have been proposed to explain the association between RA and depressive manifestations: 1) the functional disability and poor quality of life could provoke the emergence of depressive symptoms or 2) a common neuroimmunobiological mechanism could underlie the development of RA and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Частота РТДС варьирует в работах разных авторов от 15 до 89% [3,[7][8][9][10], что связано не только с особенностями выборки, но и с различными способами их ди-агностики. В большинстве исследо-ваний диагностика РТДС проводит-ся с помощью опросников, которые, являясь достаточно субъективным инструментом оценки, как правило, занижают реальную частоту депрес-сивных и тревожных расстройств.…”
Section: Discussionunclassified
“…Частота встречаемости депрессивных рас-стройств при РА достигает 40-70%, в том числе большой депрессии (БД) -порядка 13-30%, а ТР -20-46% [3,[7][8][9][10]. Распространенность всех ПР у больных РА, по дан-ным ФГБНУ НИИР им.…”
unclassified
“…The authors note that some physicians may not feel comfortable discussing depression with their patients and advocate the use of brief depression screening questionnaires before the patient's visits in order to identify problems early on. The prevalence of anxiety has been less well studied in this population (Soderlin et al, 2000;VanDyke et al, 2004), though there is some evidence that anxiety may be even more common than depression (El-Miedany et al, 2002), a conservative estimates of the prevalence of coexisting somatic disorders and phobias, according to Hansen's study was 12.9%. Psychiatric syndromes have significant implications for patients with rheumatoid arthritis: individuals with both arthritis and depression report increased functional disability (Vali et al, 1998) and increased levels of arthritis-related pain (Fifield et al, 1998), compared to individuals with arthritis alone.…”
Section: Psychiatic Morbidity In Rheumatoid Arthritismentioning
confidence: 96%